Edukasi Anti-Bullying dalam Membangun Karakter Santri Berakhlak Mulia di Taman Pendidikan Quran (TPQ) dan Madrasah Diniyah (Madin) Al Falah Pasuruan - Ariyanti, Novi; Winarti, Endah (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Bullying, both physical and psychological, has a significant impact on the development of both victims and also perpetrators. This issue is often found not only in formal educational institutions but also in non-formal education settings such as Al-Qur'an Education Center. and Supplementary Islamic School. This community service activity aims to raise awareness among students, teachers, and parents about the importance of preventing bullying through educational seminars, role-playing activities, and interactive discussions. Using Participatory Action Research (PAR) is a participatory research approach that involves the surrounding community at TPQ (Taman Pendidikan Qur’an) and Madrasah Diniyah (Madin) Al Falah Pasuruan, as well as the teachers as active subjects, not merely research objects. This program involves 200 students from TPQ and Madin Al-Falah, as well as the active participation of 25 teachers to develop joint strategies in building the character of students with noble morals through education on preventing bullying actions. The outcomes of this program include increased understanding of bullying, the creation of an anti-bullying code of ethics, and greater community participation in bullying prevention.